The Beighton score as a predictor of Brighton criteria in sport and dance. (July 2018) - Armstrong, Ross; Greig, Dr Matt
Abstract: Objectives: To determine the efficacy of using the Beighton joint hypermobility score as a predictor of Brighton criteria components, considering the influence of gender and sports participation. Design: Cross sectional study design. Setting: A University. Participants: Sixty-five female rugby players, 38 male rugby players, 61 netball players, 42 female dancers, 40 male controls and 40 female controls. Main outcome measures: The Beighton score was assessed using the Beighton and Horan Joint Mobility Index. The Brighton criteria was used to assess joint hypermobility syndrome. A binary logistic regression was performed for a pooled sample (n = 286), and subsequently for gender and sport to assess the Beighton score as a predictor of Brighton criteria. Results: Beighton scores were found to be a predictor of arthralgia (P = 0.002), dislocation and subluxation (P = 0.048) in the pooled analysis; a predictor of dislocation and subluxation (P = 0.047) in males and arthralgia (P = 0.001) in females. Beighton scores were a predictor of arthralgia in female rugby (P = 0.003) and in female controls (P = 0.012). Conclusions: The potential of the Beighton score to predict joint arthralgia and dislocation/subluxation may allow clinicians to implement effective injury prevention strategies. Highlights: The Beighton score was a predictor of arthralgia and dislocation in pooled group analysis. The Beighton score was a predictor of joint dislocation/subluxation in males. The Beighton score was a predictor of joint arthralgia in females. The Beighton score was a predictor of joint arthralgia in female rugby players and female controls. The Beighton score can be used to predict joint arthralgia and dislocation/subluxation and may aid injury prevention.